Effectiveness of Giving Papaya Leaf on The Fluence of Breast Milk in Breastfeeding Mothers at Nimasi Health Center at The Year of 2022 - Kristina Aquilina Nahak; Ramatian Simanihuruk; Maria Nafrida Ampu (Institute of Computer Science (IOCS), 2022)
Mother's Milk (ASI) is the best life liquid that is needed by babies. Breast milk contains various substances that are important for the growth and development of babies and according to their needs. Papaya leaf extract contains high protein and calories, thus affecting the volume of breast milk produced. To find out the description before and after giving papaya leaf vegetable to the smoothness of breastfeeding in breastfeeding at the Nimasi Health Center in 2022. This type of research is a quasi-experimental research with a One Group Pretest-Postest Design approach without control. The location of this research was carried out at the Nimasi Health Center which started from April 1-April 5 by visiting residents' houses . The sample in this study were 15 breastfeeding mothers. Frequency the smoothness of breast milk before given papaya leaf vegetable is obtained score average 5,33 and breastfeeding frequency after giving papaya leaves obtained average 12.0 There influence gift papaya leaf vegetable on the smoothness of breast milk in nursing mothers obtained P-value = 0.000. There is effectiveness of giving papaya leaf vegetable before and after the intervention of giving papaya leaf vegetable . Therefore it is recommended for breastfeeding who experience breast milk is not smooth to consume papaya leaf vegetables to facilitate breast milk.